2021
DOI: 10.3389/fcell.2021.737304
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Riboside and Metformin Ameliorate Mitophagy Defect in Induced Pluripotent Stem Cell-Derived Astrocytes With POLG Mutations

Abstract: Graphical AbstractHypothetical mechanisms of mitophagy dysfunction in POLG-mutant astrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Our study not only revealed the loss of neurons but also highlighted the presence of astrocyte activation and reactive gliosis in patient-derived organoids. The observed astrocyte activation is particularly significant as it has been shown in our study [43] and previous research [44] to be associated with neuronal toxicity and may contribute to the neural loss observed in POLG-related disorders. Astrocytes play crucial roles in supporting neuronal function and maintaining brain homeostasis.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our study not only revealed the loss of neurons but also highlighted the presence of astrocyte activation and reactive gliosis in patient-derived organoids. The observed astrocyte activation is particularly significant as it has been shown in our study [43] and previous research [44] to be associated with neuronal toxicity and may contribute to the neural loss observed in POLG-related disorders. Astrocytes play crucial roles in supporting neuronal function and maintaining brain homeostasis.…”
Section: Discussionsupporting
confidence: 69%
“…In the realm of therapeutic interventions for POLG-associated disorders, the role of metformin as a treatment option has garnered considerable attention. Building on our previous work, we’ve substantiated its effectiveness through an array of tests [28]. A closer examination of metformin’s potential therapeutic pathways reveals its intimate association with mitochondrial operations and cellular metabolic processes.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Functional validation studies using appropriate in vitro disease models recapitulating the neuropathological features of mitochondrial epilepsy, including parvalbumin+ interneuron vulnerability, should also be performed to overcome the limitations of using postmortem tissues to determine the cause and effect of parvalbumin+ interneuron dysfunction and degeneration [32]. Suitable models could then be utilised to test novel therapies which improve the functioning of parvalbumin+ interneurons and consider the interactions with nonneuronal cells including astrocytes which potentially have a neuropathological role in POLG-related disease [32,62,63]. It is likely that novel treatments targeting mitochondria to prevent the dysfunction of these highly important organelles and to preserve the functioning of parvalbumin+ interneurons may benefit an array of patients with common epilepsies and neurodevelopmental disorders.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…19 Mitochondria-specific autophagy (mitophagy), a cellular catabolic process targeting damaged mitochondria, holds a prominent role in mitochondrial quality control 20 and is dysregulated in aortic aneurysms. 21,22 Chen et al 23 showed that both treatment with NR or with metformin, an antidiabetic drug that enhances autophagy, rescued mitophagy defects and mitochondrial function in mitochondrial DNA polymerase gamma (POLG)-mutant cells. In fact, there is strong evidence about the protective effect of metformin on abdominal aortic aneurysm growth and rupture in humans and ApoE-mouse models.…”
Section: Resultsmentioning
confidence: 99%